Analysis of MR Signs to Distinguish Between ARCO Stages 2 and 3A in Osteonecrosis of the Femoral Head. Issue 2 (26th July 2021) - Shi, Shan; Luo, Ping; Sun, Li; Zhao, Yanping; Yang, Xuedong; Xie, Limin; Yu, Tong; Wang, Zhenchang
Abstract : Background: MRI is the most effective diagnostic tool of osteonecrosis of the femoral head (ONFH), especially for early diagnosis, but its detection of subchondral or cortical fractures is less accurate than CT. Therefore, it is difficult to accurately stage ONFH in the peri‐collapse period by MRI. Purpose: To improve the accuracy of MR for distinguishing between Association Research Circulation Osseous (ARCO) stages 2 and 3A in ONFH. Study Type: Retrospective. Subjects: One hundred and fifty five cases of ARCO stage 2/3A of ONFH underwent MR examinations, M/F = 72/83. CT was used as reference standard for collapse, which was decided by an orthopedist and a radiologist in consultation. Field Strength/Sequence: 3 T/axial and coronal T1 ‐weighted Turbo Spin Echo (T1 W TSE) sequence, axial T2 ‐weighted fat‐saturated (T2 W FS) TSE sequence, and coronal proton density‐weighted imaging (PDWI)‐FS‐Dixon fat/water image. Assessment: Five potential MR signs (the maximum width of the necrotic‐viable interface, bone marrow edema (BME), irregular articular surface of the femoral head, T2 heterogeneous high signal, and the absence of a necrotic‐viable interface with the morphology of closed loop) were evaluated blindly by five radiologists independently and the total scores of different combinations of MR signs were calculated. Statistical Tests: Mann–Whitney U test and Chi‐square test were used to evaluate age, gender, and MR signs differences between the two groups. ROC curve was used to access the distinguishing value of MR signs. The consistency of the five radiologists was analyzed by intraclass correlation coefficient. Results: The area under the curve of the combined MR signs 2 for distinguishing between ARCO stages 2 and 3A was the greatest (0.967), sensitivity and specificity were 100.00% and 88.71% respectively, and greater than 1 was the threshold. Data Conclusion: Combined MR signs 2 has great values in distinguishing between ARCO stages 2 and 3A in ONFH, thus helping clinical therapy. Level of Evidence: 4 Technical Efficacy: Stage 2